Proust og det frynsede selv - Tygstrup, Frederik (Passage - Tidsskrift for litteratur og kritik, 2015)
Frederik Tygstrup: “Proust and the Literary Lacination of the Self” This essay investigates the mode of social and sensual experience developed by Marcel Proust in his novel In Search of Lost Time. The main hypothesis is that in Proust, the traditional understanding of experience as a relation between an experiencing subject and an experienced object is replaced by a more complex process of interaction and blending between the two, resulting in a concomitant fragmentation of the object and lacination of the subject. The first part of the essay is a theoretical inquiry into the notion of experience, based on a re-reading of Gilles Deleuze’s influential interpretation of Proust in Proust and Signs from 1964, with special attention to the affective nature of experience. On this basis, the second part undertakes a close reading of a few passages taken from the early part of the novel to demonstrate how experience is actually conceived in Proust and, of no less importance, how this conception is underpinned by specific and characteristic features of Proust’s prose style.